Dietary Adherence to Long-Term Controlled Feeding in a Calorie-Restriction Study in Overweight Men and Women - Moreira, Emilia Addison Machado (Nutr Clin Pract, 2011)
BACKGROUND: The success of clinical dietary interventions depends on the motivation and willingness of study participants to adhere to the prescribed or provided diet. The aim of this study was to assess participants’ adherence to their provided diet over the 6-month duration of the Comprehensive Assessment of Long-term Effects of Reducing Intake of Energy (CALERIE). METHODS: Investigators assessed the dietary adherence of 46 men and women who completed the first phase of the CALERIE trial. Volunteers were randomized to 1 of 4 dietary intervention groups: control, calorie restriction, calorie restriction with exercise, and low-calorie diet. Participants were provided with foods during 2 weeks of baseline and during the first 12 weeks and the last 2 weeks of the intervention as outpatients, and they completed a daily self-report form to assess diet adherence. The data are expressed as mean ± standard deviation or standard error of the mean. Pearson’s correlation coefficient was determined to examine the relationship between assigned energy levels and total energy intake. RESULTS: Deviations reported were for eating nonstudy foods as well as not eating study foods. There were few deviations, and when converted to mean calories per day these did not affect total energy (weeks −3 to 2 = 10.25 ± 4.82, weeks 1–4 = 9.93 ± 12.52, weeks 5–11 = 8.38 ± 7.42, weeks 22–23 = 0.53 ± 3.97 kcal/d). The associations between assigned energy level and actual intake were high for all groups (P = .001), weeks −3 to −2 (r = 0.999), weeks 1–4 (r = 0.998), weeks 5–11 (r = 0.999), and weeks 22–23 (r = 0.998). CONCLUSIONS: The data provide evidence that dietary adherence is good when all foods are provided and when participants are highly motivated.